2005
DOI: 10.1145/1061347.1061354
|View full text |Cite
|
Sign up to set email alerts
|

ABF++: fast and robust angle based flattening

Abstract: TechnionConformal parameterization of mesh models has numerous applications in geometry processing. Conformality is desirable for remeshing, surface reconstruction, and many other mesh processing applications. Subject to the conformality requirement, these applications typically benet from parameterizations with smaller stretch. The Angle Based Flattening (ABF) method, presented a few years ago, generates provably valid conformal parameterizations with low stretch. However, it is quite time consuming and becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
196
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(200 citation statements)
references
References 30 publications
2
196
0
2
Order By: Relevance
“…Iterative? Shape-preserving [6] Fixed Yes No MIPS [16] Free Yes Yes ABF/ABF++ [33,34] Free Local (no flips) Yes LSCM/DNCP [4,23] Free No No Holomorphic 1-form [12] Fixed No No Mean-value [7] Fixed Yes No Yamabe Riemann map [26] Fixed Yes Yes Circle patterns [22] Free Local (no flips) Yes Genus-0 surface conformal map [19] Free No Yes Discrete Ricci flow [20] Fixed Yes Yes Spectral conformal [27] Free No No Generalized Ricci flow [36] Fixed Yes Yes Two-step iteration [3] Fixed Yes Yes [13] and an iterative scheme for genus-0 surface conformal mapping in [12] to obtain a planar conformal parameterization. In [27], Mullen et al reported a spectral approach to discrete conformal parameterizations, which involves solving a sparse symmetric generalized eigenvalue problem.…”
Section: Methodsmentioning
confidence: 99%
“…Iterative? Shape-preserving [6] Fixed Yes No MIPS [16] Free Yes Yes ABF/ABF++ [33,34] Free Local (no flips) Yes LSCM/DNCP [4,23] Free No No Holomorphic 1-form [12] Fixed No No Mean-value [7] Fixed Yes No Yamabe Riemann map [26] Fixed Yes Yes Circle patterns [22] Free Local (no flips) Yes Genus-0 surface conformal map [19] Free No Yes Discrete Ricci flow [20] Fixed Yes Yes Spectral conformal [27] Free No No Generalized Ricci flow [36] Fixed Yes Yes Two-step iteration [3] Fixed Yes Yes [13] and an iterative scheme for genus-0 surface conformal mapping in [12] to obtain a planar conformal parameterization. In [27], Mullen et al reported a spectral approach to discrete conformal parameterizations, which involves solving a sparse symmetric generalized eigenvalue problem.…”
Section: Methodsmentioning
confidence: 99%
“…There are many different unwrapping methods to map a 3D mesh to a 2D plane to produce a parameterization [2], [6], [11], [19]- [22]. To a great extent, they all are able to produce an initial parameterization.…”
Section: B Bar-net Based Initial Parameterizationmentioning
confidence: 99%
“…Bump mapping stores small deviations of the pointwise normal from that of the smooth underlying surface and uses the perturbed version during shading [13]. Normal mapping [118,130] is a similar technique that replaces the normals directly rather than storing a perturbation. As the light direction changes, the shading variations produced by the normal perturbations simulate the shadows caused by small pits and dimples in the surface.…”
Section: 1)mentioning
confidence: 99%
“…For such applications the bijectivity requirement can be weakened, requiring only local rather than global bijectivity. Local bijectivity [118] requires a map of any sufficiently small region of the mesh to be bijective. This condition is violated when the mappings of adjacent mesh triangles intersect, in this case the parameterization is said to "fold over" or contain "triangle flips" (Figure 2.1(b)).…”
Section: Terminologymentioning
confidence: 99%
See 1 more Smart Citation